Studies on cocopeat, sawdust and dried cow dung as desiccant for evaporative cooling system. (November 2019) - Singh, Ashutosh; Kumar, Sunil; Dev, Rahul
Abstract: The aim of the present study was to investigate the ability of natural materials, such as dried cow dung, cocopeat, and sawdust to be used as a desiccant in the evaporative cooling system to reduce the inlet air humidity. Moisture sorption and desorption characteristics of these natural materials were found out and also compared with that of silica gel. These materials were tested in different air conditions to know the sorption (28° C-85% RH, 28° C-60% RH, 33° C-60% RH) and desorption characteristics (50° C-10% RH). The materials' behavior in different humidity with the same temperature; and the same humidity with different temperature was also studied. These natural materials were studied to replace costly chemical desiccants, such as silica gel, zeolites, etc. Experimental results confirmed that cocopeat and dried cow dung have the potential to replace the chemical desiccants based on their sorption and desorption characteristics while sawdust was not found to have the desired characteristics of good desiccant. These natural materials (considered as waste) are cheap, and their reutilization will also be helpful to minimize the waste management problem. Highlights: Natural materials, such as dried cow dung, cocopeat, and sawdust tested. Sorption and desorption characteristics of the natural materials studied. Cocopeat and dried cow dung have the potential to replace the chemical desiccants. Increase in sensible heat load by natural materials was less than silica gel.